Prevalence and Risk Factors of Home Quarantine Strategy Implementation Among Chinese Residents During the Coronavirus Disease 2019 Pandemic - Li, Liqing; Shen, Xin; Zhou, Xiaogang; Cao, Hui; Feng, Jing; Lei, Zihui; Tian, Kunming; Liang, Jiarui; Wang, Yuan; Lu, Zuxun; Gan, Yong (Frontiers in Psychology, 2021)
Background: Home quarantine is an important strategy to contain the mass spread of the coronavirus disease 2019 (COVID-19) pandemic. However, there is a dearth of studies on the prevalence and risk factors of home quarantine strategy implementation among residents. This study aims to assess the state of home quarantine strategy implementation among Chinese residents, which could provide a reference for quarantine policymakers around the world during the pandemic. Method: We conducted a cross-sectional survey of 3398 residents in China by adopting a convenience sampling strategy. We measured the prevalence and risk factors of home quarantine strategy implementation with the Center for Epidemiological Studies-Depression Scale (CES-D), 10-item Connor-Davidson Resilience Scale (CD-RISC 10), and Perceived Social Support Scale (PSSS). A multivariable model was used to determine the factors associated with home quarantine strategy implementation. Results: A total of 2936 (86.4%) respondents carried out home quarantine. There were some factors significantly associated with home quarantine strategy implementation among Chinese residents during the COVID-19 outbreak. Respondents who were male, lived in western and central China, were aware of the primary symptoms of COVID-19, were willing to accept recommendations on relevant protective measures, understood local quarantine measures, had better resilience, and had better social support were more likely to engage in home quarantine. Respondents who were married, were employed, were healthy and had high depression scores were more likely to refuse to follow home quarantine guidance. Conclusions: Gender, region, marital status, employment status, health status, awareness of the primary symptoms of COVID-19, willingness to accept recommendations on relevant protective measures, understanding of local quarantine measures, depression, psychological resilience and perceived social support were the main factors affecting the implementation of residents' home quarantine strategy. Health service policymakers should adopt relevant measures to improve the prevalence of home quarantine strategy implementation among residents during the pandemic.